Applications of Nanomaterials in Energy Systems (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This comprehensive reprint explores the remarkable advancements in energy-related systems driven by the utilization of nanomaterials. It covers a wide range of topics, from material-level investigations to device-level applications, incorporating molecular dynamic simulations and measurements of electrical, thermal, dielectric, and electrochemical properties. The chapters delve into optimizing heat transfer processes, enhancing HVAC systems, improving Li-ion battery performance, developing high-performance carbon nanofiber anodes, and exploring the potential of flexible porous silicon/carbon fiber anodes. The reprint also discusses formic acid microfluidic fuel cells, 2D MXenes, electrical breakdown models, nanocomposite capacitors, and the dielectric behavior of nanofluids. It addresses topics such as radical scavenger fillers, the thermal properties of ternary nitrate, distributed Bragg reflectors, Pd–Pt bimetallic dendrites, and the oil–water interface behavior of modified graphene oxide. With its multidisciplinary approach and comprehensive coverage, this reprint serves as a valuable resource for researchers, scientists, and engineers working in the field of energy-related systems and nanotechnology.